Efficacy of lung volume optimization maneuver monitored by optoelectronic pletismography in the management of congenital diaphragmatic hernia. (2017) - Lista, G.; Bresesti, I.; Cavigioli, F.; Castoldi, F.; Lupo, E.; LoMauro, A.; Aliverti, A.
Abstract: Newborns affected by congenital diaphragmatic hernia (CDH) need cardio-respiratory stabilization before undergoing surgical repair. Open lung strategy is a well-established approach to optimize lung volume in preterm infants with Respiratory Distress Syndrome (RDS), using both High Frequency Oscillatory Ventilation (HFOV) and Conventional Mechanical Ventilation (CMV). We report a case of left CDH with severe lung hypoplasia, managed applying open lung strategy in HFOV (pre-surgery period) and in Assist-Control with Volume Guarantee (post-surgery period), guided by SpO2 changes, TcPO2 and TcPCO2 monitoring. Opto-electronic plethysmography was used to measure end-expiratory chest wall volume changes (ΔEEcw) related to lung volume variations occurring during pressure changes. OEP confirmed the efficacy of using SpO2 and transcutaneous gas monitoring during this recruitment maneuver.